Fractional-order Sliding Mode Constraint Control for Manipulator Systems Using Grey Wolf and Whale Optimization Algorithms - Han, Seong-Ik (International journal of control, automation, and systems, 2021)
This study investigates a new fractional-order nonsingular terminal sliding mode control (FTSMC) leveraging a finite-time extended state observer, a simpler prescribed control, and hybrid grey wolf optimization (GWO) combined with whale optimization algorithm (WOA) for manipulator systems. The new FTSMC system is based on an improved fractional-order terminal sliding surface. Initially, the study experimentally optimizes the dynamic parameters and gains of the controller and the observer with the help of the newly developed GWO-WOA technique. As the next step, the uncertainties including optimization error and external disturbances are estimated by the finite-time extended state observer designed using the sliding mode dynamics. Experimental results of GWO-WOA optimization and joint position tracking for a self-designed articulated manipulator prove the efficacy of the proposed control scheme.